BIOSAFETY ASSESSMENT OF MgAl LDH-ANACARDIC ACID COMPLEX ON SWEET MUSTARD (BRASSICA INTEGRIFOLIA) AND MICE - Nhu Quynh, Nguyen Thi; Van Anh, Le Thi; Hung, Nguyen Huu; Chien, Hua Quyet; Thang, Nguyen Tien (Vietnam Journal of Biotechnology, 2018)
MgAl layered double hydroxides adsorbed anacardic acid (L-A complex) nanomateial used as a biological pesticide, could kill cutworms larvae (Spodoptera litura). This study assessed the effect of the MgAl layered double hydroxides, anacardic acid, and L-A complex on growth and development of sweet mustard trees, their toxicity on mice and the anacardic acid substance residues of L-A complex on sweet mustard trees (Brassica integrifolia) using HPLC method. The results showed that the MgAl layered double hydroxides and L-A complex did not affect the growth indexes including body height, root length, fresh weight, dry weight and chlorophyll concentrations of sweet mustard when killing larvae dose of 0,148 mg/mL was applied to the plants. The toxicity evaluation on mice indicated LD50 values of anacardic acid was 2378,41 mg/kg body weight, while no mice died from using L-A complex with anacardic acid concentration of 2553 mg/kg body weight. These results indicated that the toxicity of anacardic acid was reduced as using anacardic acid with MgAl layered double hydroxides in comparison with using anacardic acid alone. In testing the toxicity of free LDH, at dose applying on mice 6000 mg/kg body weight, no death mice or any abnormal behaviors of them was recorded. The result also showed that the anacardic acid residues in mustard leaves decreased from 40,6 mg/kg to 15,7 mg/kg leaves after 6 days. Therefore, all the results indicated that LDH, anacardic acid and L-A complex had no acute toxicity in mice and negative effect on growth and development of mustard plant. Prospectively, anacardic acid and L-A complex can be used as biological pesticides and safety materials in agriculture.